Back Cover: A Unified Approach for the Total Synthesis of cyclo‐Archaeol, iso‐Caldarchaeol, Caldarchaeol, and Mycoketide (Angew. Chem. Int. Ed. 32/2021). Issue 32 (21st June 2021) - Andringa, Ruben L. H.; de Kok, Niels A. W.; Driessen, Arnold J. M.; Minnaard, Adriaan J.
Abstract : Archaeal lipids have been prepared by iridium‐catalysed asymmetric hydrogenation, as reported by Adriaan J. Minnaard et al. in their Research Article on page 17497 . Geranylgeraniol, extracted from Bixa orellana seeds, flows in the carafe with the iridium catalyst. The carafe symbolises Iris, the Greek goddess of the rainbow, after which iridium has been named. The final products are poured from it. Mycoketide, produced by M. tuberculosis, is depicted with a picture of the bacterium. The membrane‐spanning lipids are represented by glucosylated caldarchaic acid, the grand prismatic spring in Yellowstone, and a picture of the prepared giant unilamellar vesicles.